Ethnopedagogy of the Rambu Solo Ceremony in the Toraja Hindu Community in West Sulawesi - Ni Ketut Ratini; Wayan Paramartha; I Gusti Ayu Suasthi (UNHI PRESS, 2025)
Every religion believed by the community has its own tradition or culture, as the identity of the community. Culture is one of the reflections that maintain world civilization. So that the existence of human wisdom is maintained, one of the cultures that still exists from the Toraja tribe which is very unique is the Rambu Solo Ceremony. The uniqueness of the Rambu Solo Ceremony is the technique of treating the bodies of people who have died, in this case some are buried, some are preserved first in chests, some are stored in caves, and some are stored in special houses or burrows. The Rambu Solo ceremony also makes animal sacrifice offerings, including buffaloes and pigs in fantastic numbers, the animal offerings number up to hundreds of heads, and have an economic value of hundreds of millions and even billions of rupiah. This practice is an effort to give the last respect to the ancestors, where this custom or Rambu Solo Ceremony is a traditional funeral ritual that must be carried out by the Aluk Todolo community, this ceremony is an itangible cultural heritage, which is a custom that has been passed down for years from their ancestors. This then attracts the author to answer these three problems: (1) Why the Ethnopedagogy of Rambu Solo Ceremony in Toraja Hindu community can survive, (2) How is the process of Ethnopedagogy of Rambu Solo Ceremony, (3) How is the implication of Ethnopedagogy of Rambu Solo Ceremony on knowledge, attitude, and behavior of Toraja Hindu community. Research objectives: (1) To analyze the survival of Rambu Solo Ceremony Ethnopedagogy in Toraja Hindu community, (2) To analyze the process of Rambu Solo Ceremony Ethnopedagogy, (3) To analyze the implication of Rambu Solo Ceremony Ethnopedagogy. Three theories are used in this research: (1) structural functionalism theory, (2) constructivistic theory, and (3) meaningful learning theory. This type of research is qualitative, how to determine informants by purposive sampling, data collection techniques include: Observation, interview, document study, and literature study. The results of this research analysis strengthen the postulates of structural functionalism theory where the Rambu Solo Ceremony is not only a religious ritual, but an educational process that plays an important role in maintaining the social and cultural structure of society, this is in line with the AGIL scheme (Adaptation, Goal attaement, Integration, and Latency), but has not been able to fully overcome the external situation (latency) which can eliminate the ethnopedagogical existence of the Rambu Solo Ceremony.